Industrial design, competition and globalization - Bryson, J. R. , 1963-; Rusten, Grete (Palgrave Macmillan, 2010)
"Design plays an increasingly important role in the competitiveness of firms. Increasingly price-based competition is being replaced by business models based around design and added value. Given the importance of design in corporate competitiveness, this book explores the importance of industrial design within the contemporary economy"--Provided by publisher.